Internal carburisation of an industrial alloy: a quantum chemical study of microstructure's changes - Lanz, César Armando (2013)
A quantum chemical theoretical study on the chemical bonding and electronic structure of the γ-FeNiCr–C interaction is performed using the Atom Superposition and Electron Delocalisation method in order to contribute to the understanding of the changes in the alloy microstructure caused by carburisation phenomenon. A complementary analysis of a HK-40 structure changes after service is also presented by using optical and electron microscopy techniques.